531 (mis)using randomised controlled trials as a hegemonic weapon: the case of mandatory influenza vaccination for healthcare workers in canada. (24th April 2018) - Yassi, Annalee; Lockhart, Karen
Abstract : Introduction: In 2013, British Columbia, Canada, instituted a Policy requiring healthcare workers (HCWs) to accept influenza vaccination or wear a mask at work throughout the influenza season. The Policy's stated objectives (prevent influenza transmission to vulnerable patients; reduce influenza morbidity and mortality; and reduce worker absenteeism) did not refer to the health of HCWs. Moreover, the four randomised controlled trials (RCTs) cited as evidence supporting this influenza vaccine-or-mask policy were misinterpreted (or misrepresented) by its proponents, which, we argue, not only threatens the health of workers, the public and patients, but jeopardises the credibility of public health institutions. Methods: Plausibility of the four RCT findings attributing indirect patient benefits to HCW influenza vaccination were assessed by international experts comparing percentage reductions in patient risk reported by the RCTs to predicted values; we synthesise the results of the analysis and discuss the political factors that may explain the (mis)use of the RCT evidence. Result: Each RCT violated the basic mathematical principle of dilution by reporting greater percentage reductions with less influenza-specific patient outcomes and/or patient mortality reductions exceeding even favourably derived predicted values by at least 6–15-fold. Contextual factors more likely to explain the RCT results were ignored. The prioritisation of quantitative data masks the economic and political agendas of policy makers. Discussion: This policy is a case of (mis)use of RCT evidence as a weapon against workers while transferring large amounts of public funds to a questionable program and ultimately to pharmaceutical companies. We argue that worker acceptance of influenza vaccination should be voluntary, and public resources be more appropriately allocated to measures more likely to result in greater public health benefit, such as improved sick leave to encourage ill workers to stay home, or more staffing to allow HCWs to be more vigilant with infection control procedures.